Incorporating torch ginger (Etlingera elatior Jack) inflorescence essential oil onto starch-based edible film towards sustainable active packaging for chicken meat - Marzlan, Anis Asyila; Muhialdin, Belal J.; Zainal Abedin, Nur Hanani; Manshoor, Nurhuda; Ranjith, Fernando H.; Anzian, Aliaa; Meor Hussin, Anis Shobirin (Elsevier, 2022)
Incorporating torch ginger (Etlingera eliator Jack) inflorescence essential oil (TGIEO) in active packaging could offer protection to enhance safety and extend chicken meat's shelf life. Thus, the study’s objectives were to evaluate the antioxidant, antibacterial and physicochemical activities of TGIEO incorporated into a starch-based edible film (TF) for chicken meat packaging. The films were prepared by casting method and were exposed to light absorption at 200–800 nm for the light barrier and opacity properties. The water aspects, thermal analysis by differential scanning calorimetry, antioxidant activities, antimicrobial activities, and biodegradability of the film in vegetable compost were determined. Next, the coliform count, rancidity test, and 9-point hedonic scale sensory analysis for chicken meat packed with TF were evaluated. Results shows TF with higher opacity value (3.168 ± 0.03–9.024 ± 0.09), lower water solubility (0.070 ± 0.09% - 0.095 ± 0.00%) and can withstood temperatures at < 280 °C. The diphenyl-2-picryl-hydrazyl (DPPH) and 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS+) showed antioxidant activity at 67.36 ± 2.48% and 84.78 ± 0.57%, respectively. For antibacterial activities, TF showed positive inhibition towards pathogenic bacteria; Bacillus subtilis, Staphylococcus aureus, Listeria monocytogenes, Salmonella Typhi, and Escherichia coli (6.0 ± 0.01–23.0 ± 0.12 mm) and exhibited significant observation for degradation in vegetal compost after 10 days. At the end of the chilled storage period (3 °C ± 1), the chicken sample TF showed the lowest coliform count (4.98 ± 0.07 CFU/g) and thiobarbituric acid reactive substances (TBARS) value (0.212 ± 0.31 mg MDA/kg). There is no significant difference (p < 0.05) for all the chicken samples for sensory analysis and concluded that the TGIEO does not affect the organoleptic properties. Thus, the TF showed significant antibacterial and antioxidant film properties that potentially extend the quality of chicken meat during the chilled storage period.